The president is missing a novel - Clinton, Bill. (New York Little Brown & Company, 2018)
The President Is Missing confronts a threat so huge that it jeopardizes not just Pennsylvania Avenue and Wall Street, but all of America. Uncertainty and fear grip the nation. There are whispers of cyberterror and espionage and a traitor in the Cabinet. Even the President himself becomes a suspect, and then he disappears from public view . . .
Keywords: Missing persons--Fiction.